Dietary phosphorus requirement of GIFT strain of Nile tilapia Oreochromis niloticus reared in freshwater. (25th November 2013) - Yao, Y.F.; Jiang, M.; Wen, H.; Wu, F.; Liu, W.; Tian, J.; Yang, C.G.
Abstract A study was conducted to estimate the optimum requirement of dietary available phosphorus for GIFT strain of Nile tilapia Oreochromis niloticus. Six purified diets were formulated to contain graded levels (0 (control diet), 2.9, 4.8, 7.6, 9.1 and 10.9 g kg−1 diet) of available phosphorus. Each diet was fed to triplicate groups of 12 fish with initial average weight (46.03 ± 2.14) g for 8 weeks. The results showed that fish fed the three lowest phosphorus diets (0, 2.9 and 4.8 g kg−1) had significantly lower weight gain rate, specific growth rate (SGR) and feed efficiency than those fed the other diets (P < 0.05). The survival rate of fish fed the control diet was significantly lower than that of the fish fed the other diets (P < 0.05). Whole body viscerosomatic index and crude lipid content decreased significantly with increasing dietary available phosphorus levels (P < 0.05), while the contents of crude ash, calcium, phosphorus in the whole body and vertebrae showed the opposite trend (P < 0.05). The blood chemistry analysis showed that dietary available phosphorus had significant effects on serum phosphorus concentration, enzyme activities of alkaline phosphatase and parathyroid hormone level. Quadratic curve analysis based on SGR indicated that the minimum dietary requirement of available phosphorus for maintaining optimal growth of tilapia was 8.6 g kg−1.